Whole genome sequencing and taxonomic profiling of two Pantoea sp. isolated from environmental samples in Israel - Yehoudit Guedj-Dana; Inbar Cohen-Gihon; Ofir Israeli; Ohad Shifman; Tamar Aminov; Shahar Rotem; Raphael Ber; Anat Zvi (BMC Genomic Data, 2022)
Abstract Objective As part of a research aiming at the isolation of bacteria secreting growth inhibiting compounds, cultures of Francisella tularensis were implanted in environmental samples and monitored for inhibition zones on agar. Two antibiotic-like secreting bacteria were isolated, their genomic sequence was deciphered and taxonomic profiling analysis classified them as belonging to the Pantoea genus. Data description Two bacterial isolates exhibiting growth inhibition zones to F. tularensis (LVS) were analyzed using the Oxford Nanopore Technology (ONT). Preliminary de novo assembly of the reads was performed, followed by taxonomic profiling based on Multi Locus Sequence Analysis (MLSA) and implementation of the Average Nucleotide Identity (ANI) measure. The genomic sequences resulted in the identification of two different Pantoea species, denoted EnvD and EnvH. Subsequent de novo genome assembly generated 5 and 10 contigs for EnvD and EnvH, respectively. The largest contig (4,008,183 bps and 3,740,753 bps for EnvD and EnvH, respectively), overlaps to a major extent to the chromosome of closely related Pantoea species. ANI values calculated for both isolates revealed two apparently new species of the Pantoea genus. Our study deciphered the identity of two bacteria producing antibiotic-like compounds, and the genomic sequence revealed they represent distinct Pantoea species.